1982
DOI: 10.1128/iai.38.1.282-291.1982
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Streptococcus mutans Mutants with Altered Cellular Morphology or Chain Length

Abstract: A nitrosoguanidine-induced mutant, designated UAB90, of Streptococcus mutans PS14 (serotype c) strain UAB62, was identified on the basis of its unique colony morphology and isolated on brain heart infusion agar. Other mutants displaying similar colony morphologies on brain heart infusion agar were isolated after ethyl methane sulfonate mutagenesis of UAB62 and S. miltans 6715 (serotype g) strains UAB61 and UAB66, and these were found to exhibit abnormalities in cell morphology, chain length, or both. All mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Similar results have been reported [or BaciUu.s .siihtilis, for which it has been shown that crude autolysin extracts prepared frotn the organism were capable of de-chaining exponentially growing cells (6). In genetic studies involving oral streptococci, it Was shown that chetnical tnutagenesis of specific eel] types resulted in the gi-owth of elongated chains almost 10 times longer than normal (16). U waŝ hypothesized that the observed increase in chain length could be caused by increased celJ-to-cell adhesion or the re-"loval of a fector that promotes dechaining.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Similar results have been reported [or BaciUu.s .siihtilis, for which it has been shown that crude autolysin extracts prepared frotn the organism were capable of de-chaining exponentially growing cells (6). In genetic studies involving oral streptococci, it Was shown that chetnical tnutagenesis of specific eel] types resulted in the gi-owth of elongated chains almost 10 times longer than normal (16). U waŝ hypothesized that the observed increase in chain length could be caused by increased celJ-to-cell adhesion or the re-"loval of a fector that promotes dechaining.…”
supporting
confidence: 82%
“…In addition, heat-treated crude extracts demotistrated no de-chaining activity cotnpared with controls. Most studies that have evaluated factors that control or infiuence bacterial chain length have itnplicated a role for autolysitis in the process (5,6,16,18). Typically, tnany autolytic acfivities have been shown to be regulated by pH (11,18).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our observation of the HM strain revealed that the chain structure of this bacterium is shorter than that of NCTC 10449. Some studies have predicted that the conditions that may affect cellular chain length may also affect adhesion (Murchison, Larrimore, Hull, & Curtiss, 1982) and aggregation (Murchison et al, 1982;Nakano, Fujita, Nishimura, Nomura, & Ooshima, 2005), both of which can contribute to virulence. Streptococcal cellular chain length and morphology are influenced by several factors.…”
Section: Discussionmentioning
confidence: 99%